2013
DOI: 10.5222/j.child.2012.132
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in Children with Recurrent Tonsillopharyngitis

Abstract: Kalp-damar sisteminin ana işlevi hücrelere yeterli oksijen ve diğer besin maddelerini sunmaktır. Kalpdamar sistemi bu işlevini kompleks bir nöro-endokrin sistem kontrolünde yapar. Dolaşım sistemindeki işlev bozukluğu sonucu dokuların gereksinimi olan oksijen ve diğer besin madde gereksinimlerinin sağlana-madığı duruma şok denir. Doku perfüzyonu bozuktur. Şokun birçok nedeni olmasına rağmen tüm şoklarda ortak nokta hücre metabolizmasının ve enerji üreti-minin bozulmasıdır (1) .Hücrelerin enerji kaynağı adenozin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 18 publications
0
23
0
2
Order By: Relevance
“…6 Furthermore, genetic polymorphism in vitamin D receptors in immune cells that results in modulation of their functions has been indicated. 38 However, both the studies by Yildiz et al 5 and Aydın et al 21 showed insignificant differences between the patients with recurrent tonsillitis and the healthy controls in regards to vitamin D receptor polymorphisms. Nonetheless, it seems that annual frequency of tonsillitis increases in patients with Ff polymorphism in the FokI receptors.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…6 Furthermore, genetic polymorphism in vitamin D receptors in immune cells that results in modulation of their functions has been indicated. 38 However, both the studies by Yildiz et al 5 and Aydın et al 21 showed insignificant differences between the patients with recurrent tonsillitis and the healthy controls in regards to vitamin D receptor polymorphisms. Nonetheless, it seems that annual frequency of tonsillitis increases in patients with Ff polymorphism in the FokI receptors.…”
Section: Discussionmentioning
confidence: 92%
“…The included studies investigated the vitamin D status (vitamin D deficiency/insufficiency) in both case and control groups. Aydın et al 21 and Nseir et al 23 indicated that the vitamin D deficiency/insufficiency was more prevalent in patients with recurrent tonsillitis as compared with the healthy group, whereas Yildiz et al 5 and Torretta et al 25 suggested that recurrent tonsillitis was not significantly associated with vitamin D deficiency/insufficiency status, as compared to controls. However, the summary ORs revealed that serum vitamin D status had a significant effect on recurrent tonsillitis (OR, 4.37; 95% CI, 2.78-6.88; P < .001; fixed-effect model; Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in school-aged children undergoing tonsillectomy due to breathing difficulty and/or recurrent tonsillitis found 78% to have 25(OH)D levels < 30 ng/ mL, and nearly 16% < 20 ng/mL [58]. Another study showed that children with recurrent episodes of tonsillopharyngitis over a 1-year period had serum 25(OH)D levels lower than healthy children [59]. Similarly, another study investigating serum 25(OH)D concentrations among children with recurrent tonsillitis observed again that 25(OH)D levels in candidates for tonsillectomy were significantly lower than those with less than three episodes per year [60].…”
Section: Pharyngotonsillitismentioning
confidence: 99%